2022
DOI: 10.1001/jamanetworkopen.2022.34870
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Antenatal Lifestyle Interventions Into Routine Care

Abstract: ImportanceLifestyle interventions in pregnancy optimize gestational weight gain and improve pregnancy outcomes, with implementation recommended by the US Preventive Services Task Force. Yet, implementation research taking these efficacy trials into pragmatic translation remains limited.ObjectiveTo evaluate success factors for implementing pregnancy lifestyle interventions into antenatal care settings in a meta-analysis, using the penetration, implementation, participation, and effectiveness (PIPE) impact metri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 147 publications
0
9
0
Order By: Relevance
“… 120 There was also a lack of understanding of reach and capacity for implementation of lifestyle interventions in pregnancy, as previously reported. 120 Included studies did not report against the TIDieR framework, so extraction of some components required subjective interpretation. In particular, there was limited information relating to gestational age at the completion of intervention or length of sessions (ie, minutes per hour), tailoring, adherence, or attrition rates, all of which limited our interpretative ability for the efficacy of these components in GWG reduction.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“… 120 There was also a lack of understanding of reach and capacity for implementation of lifestyle interventions in pregnancy, as previously reported. 120 Included studies did not report against the TIDieR framework, so extraction of some components required subjective interpretation. In particular, there was limited information relating to gestational age at the completion of intervention or length of sessions (ie, minutes per hour), tailoring, adherence, or attrition rates, all of which limited our interpretative ability for the efficacy of these components in GWG reduction.…”
Section: Discussionmentioning
confidence: 87%
“…This study also has several limitations, including a moderate to high risk of bias across most studies as previously reported and a lack in reporting of quality assurance measures, such as adherence or fidelity . There was also a lack of understanding of reach and capacity for implementation of lifestyle interventions in pregnancy, as previously reported . Included studies did not report against the TIDieR framework, so extraction of some components required subjective interpretation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Current evidence, therefore, supports the efficacy of antenatal, postpartum, and interpregnancy health behavior change interventions in diet and physical activity during pregnancy and postpartum for improving maternal and child outcomes. Key evidence gaps include that studies typically focus on intervening during either the antenatal or postpartum period but not both and that studies tend to be short in duration (6 months is the average duration), which is known to be less effective at supporting sustained health behavior change [ 19 - 21 ]. Importantly, a large research translation gap exists around achieving adequate population penetration, participation, and implementation at scale with efficacious prevention interventions [ 19 , 20 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Key evidence gaps include that studies typically focus on intervening during either the antenatal or postpartum period but not both and that studies tend to be short in duration (6 months is the average duration), which is known to be less effective at supporting sustained health behavior change [ 19 - 21 ]. Importantly, a large research translation gap exists around achieving adequate population penetration, participation, and implementation at scale with efficacious prevention interventions [ 19 , 20 , 22 , 23 ]. Limited studies have explored intervention implementation aspects beyond highly controlled clinical trials [ 19 , 23 ].…”
Section: Introductionmentioning
confidence: 99%